Sources of inflation in Mexico, 1989-2000: A multicausal error correction analysis - Esquivel, Gerardo; Razo, Raúl (Estudios Económicos de El Colegio de México, 2003)
This article analyzes the determinants of inflation in Mexico during the 1989–2000 period. Inflation is modeled as a function of deviations in the long-run relations that may exist in the monetary, labor and exchange rate markets. By using cointegration techniques, we obtain an error-correction model where money excess, wage pressure and deviations of the Purchasing Power Parity are possible sources of inflation. The model includes an inertial factor and a policy component due to government-controlled price changes in certain goods. The results show that all the factors mentioned have contributed to the determination of the inflationary dynamics in Mexico.